Trends in Interactive Media-Based Project-Based Learning (PjBL) Models in Elementary Education: A Literature Review - Ginting, Yusrina; Wasino, Wasino; Widiarti, Nuni (UIN Sunan Gunung Djati Bandung, 2025)
To examine the tendency of interactive media-based PJBL learning models in elementary schools today, the purpose of this study is to investigate the situation. This study adopts a methodology known as a literature review. The analysis of journals published between Sinta 6 and Sinta 1 is the research design. The findings of this research analysis come from journals published over the past five years on Google Scholar. There are twenty articles that seem worthy of further publication based on the analysis of article findings relevant to the keywords searched and then read in their entirety over the previous five years. The findings of the article examination, namely the interactive media-assisted PJBL learning model, have shown that it can improve the learning outcomes and creativity of elementary school students.